Catastrophic Antiphospholipid Syndrome - Rawhya R. El-Shereef; Zein El-Abedin; Rashad Abdel Aziz; Ibrahim Talat; Mohammed Saleh; Hanna Abdel-Samia; Amro Sameh; Mahmoud Sharha (Case Reports in Rheumatology)
This paper reports one case of successfully treated patients suffering from a rare entity, the catastrophic antiphospholipid syndrome (CAPS). Management of this patient is discussed in detail.